Effect of a continuous glucose monitoring-guided personalized lifestyle coaching intervention on glycemic outcomes and variability in patients with type 2 diabetes mellitus: a randomized controlled trial - Youngran Yang; Youngmin Park; Heung Yong Jin (Journal of Korean Academy of Nursing, 2026)
Purpose: This study examined the effects of continuous glucose monitoring (CGM)-guided personalized lifestyle coaching on glycemic outcomes and glycemic variability in patients with type 2 diabetes mellitus (T2DM).Methods: This three-arm randomized controlled trial was conducted in South Korea from June 2023 to November 2024. Participants were assigned to CGM alone (Intervention I, n=34), CGM-guided personalized lifestyle coaching (Intervention II, n=34), or standard diabetes education (control, n=34). The intervention lasted 3 months, with assessments at baseline and at 3, 6, and 12 months. Data were analyzed using generalized estimating equations.Results: At 3 months, glycated hemoglobin (HbA1c) and fasting plasma glucose (FPG) levels were significantly lower in both intervention groups than in the control group. Compared with the control group, HbA1c was lower by 0.78 percentage points in Intervention I (p=.008) and by 1.12 percentage points in Intervention II (p